PIN1 protects auditory hair cells from senescence via autophagy - Zhe Lv; Yanzhuo Zhang; Huan Cao; Qingjuan Liu; Xiaojuan Feng; Huan Yin; BaoShan Wang (PeerJ, 2022)
Background Age-related hearing loss is an increasing sensorineural hearing loss. But the pathogenesis of ARHL has not been clarified. Herein, we studied the role and significance of PIN1 in regulating autophagy activity in senescence HEI-OC1cells and HCs. Methods and Results C57BL/6 mice and HEI-OC1 cells were contained in our research. Transfection of plasmids and juglone were used to upregulate or inhibit the PIN 1 expression. Immunofluorescence and Western blot were used to detect the expression of PIN1, LC3, p62, p21 and p16 protein levels in the hair cells of C57BL/6 mice cochleae and HEI-OC1 cells. Senescence-associated β-galactosidase (SA-β-gal) staining was used to investigate the senescent level.The results of this study showed that the level of autophagy increased in the senescent auditory hair cells. When inhibited the autophagy level with 3-MA, the senescent HEI-OC1 cells were alleviated. The autophagy activity in senescent HEI-OC1 cells also could be reduced by overexpressing PIN1 protein. On the contrary, inhibiting PIN1 could increase the autophagy level of senescent cells and cochlear hair cells. Conclusion PIN1 might regulate autophagy activity to induce the senescent of HEI-OC1cells and HCs, which will provide a theoretical support for the prevention and treatment of age-related hearing loss.